Ionospheric response over Thailand from the 15 January 2022 eruption of the Hunga Tonga-Hunga Ha'apai volcano - Paparin Jamlongkul; Suwicha wannawichian; Larry J. Paxton; Clayton E. Cantrall; Pornchai Supnithi; Jirapoom Budtho; Michi Nishioka; Thananphat Thanakulketsarat; P. Thammavongsy (My University, 2024)
This study reports on the upper atmospheric response over Thailand to the Hunga Tonga volcano’s eruption on January 15th, 2022. The eruption occurred during the geomagnetic storm recovery phase, providing a rare comparison between effects from outside (geomagnetic storm) and inside atmosphere (volcanic eruption). About nine hours later, we observed post-eruption fluctuations in the ionosphere total electron content (TEC). TEC was recorded in Thailand approximately ten times remarkably higher than typical levels from this large perturbation. The initial impact reached Thailand with speed of ~275 m/s. Detrended TEC (dTEC) revealed mixed wave packets at various intervals. Two significant traveling ionospheric disturbance (TID) waves reached Thailand at 13 UT and 14 UT, respectively. Equatorial plasma bubbles (EPBs) were observed between 12-15 UT and 17-18 UT over Thailand. Our findings could provide insight into how communication signals over Thailand are affected by both disturbances, particularly in the case of widespread volcanic eruptions.
Keywords: Earthquake Detection and Analysis